Pengaruh Stres kerja, Motivasi Kerja, dan Kepuasan Kerja Terhadap Turnover Intention Karyawan Minimarket - Patrick Heaven; Antonius Kristian; Steven Virgus Yudistira; Jonathan Widarta Wijaya (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The level of employees' intention to leave their jobs is a crucial issue that can threaten the operational sustainability and productivity efficiency of the organization. The purpose of this study is to assess how convenience store employees' intention to leave their jobs is affected by work-related stress, motivation, and job satisfaction. Data was collected from 100 respondents selected using Convenience Sampling technique with a Likert scale-based questionnaire using quantitative techniques and multiple linear regression analysis. The findings show that job stress has a negative but insignificant impact on turnover intention. Job satisfaction and work motivation variables have a significant and negative impact on turnover intention, indicating the significance of the role of extrinsic and intrinsic factors in reducing the tendency of employees to leave an organization. This research emphasizes the need for a holistic managerial approach that addresses workplace stress, increases motivation with performance-based incentives, and improves job satisfaction with competitive pay and a positive work atmosphere. These results provide strategic direction for companies to create policies that improve productivity, operational efficiency and staff retention in the long run.